String theory and the real world : from particle physics to astrophysics : École d'été de physique des Houches, session LXXXVII, 2 July-27 July 2007 : École thématique du CNRS /: from particle physics to astrophysics : École d'été de physique des Houches, session LXXXVII, 2 July-27 July 2007 : École thématique du CNRS. (2008) - Unknown
No abstract available